Judaism and the Grand “Christian” Abstractions: Love, Mercy, and Grace - Sanders, E. P. (Interpretation, 1985)
The body of Rabbinic material that has been relied upon for the view that Pharisaism was legalistic points rather toward confidence in God's grace and toward obedience as one's appropriate response.